A new congenital multicore titinopathy associated with fast myosin heavy chain deficiency. Issue 5 (19th April 2020) - Perrin, Aurélien; Metay, Corinne; Villanova, Marcello; Carlier, Robert‐Yves; Pegoraro, Elena; Juntas Morales, Raul; Stojkovic, Tanya; Richard, Isabelle; Richard, Pascale; Romero, Norma B.; Granzier, Henk; Koenig, Michel; et al.
Abstract: Congenital titinopathies are myopathies with variable phenotypes and inheritance modes. Here, we fully characterized, using an integrated approach (deep phenotyping, muscle morphology, mRNA and protein evaluation in muscle biopsies), two siblings with congenital multicore myopathy harboring three TTN variants predicted to affect titin stability and titin‐myosin interactions. Muscle biopsies showed multicores, type 1 fiber uniformity and sarcomeric structure disruption with some thick filament loss. Immunohistochemistry and Western blotting revealed a marked reduction of fast myosin heavy chain isoforms. This is the first observation of a titinopathy suggesting that titin defect leads to secondary loss of fast myosin heavy chain isoforms.